PENGARUH MANAJEMEN LINGKUNGAN ISLAMI TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA DI SEKOLAH DASAR ISLAM AL-FURQON KABUPATEN KARAWANG - Ajat Rukajat; Masykur H.Mansyur; Nabilhaibah Qoriy Hakiki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of Islamic environmental management on improving students' academic achievement at Al-Furqon Islamic Elementary School in Karawang Regency. A learning environment managed with Islamic values is believed to create a religious, comfortable, and conducive atmosphere, which positively impacts students' cognitive, affective, and psychomotor development. The study employs a quantitative approach with a correlational method. Data collection techniques include questionnaires and documentation. The analysis results show a significant influence of Islamic environmental management—including planning, organizing, actuating, and controlling—on students' academic achievement. This research highlights the importance of integrating Islamic values into school environmental management as a strategy to enhance the quality of elementary education and shape students with noble character.